Content Analysis of Verbal Violence in Film: Crows Zero, Crows Zero II, and Crows Zero Explode - Muhammad Wahyu Ibrahim; Dewi Soraya Rachmah; Lili Sugeng Wiyantoro (Universitas Negeri Malang, 2024)
This research aims to conduct a comprehensive analysis of the frequency and distribution of verbal violence in three films: